TRIP ATTRACTION MODEL OF HOSPITALS IN PROBOLINGGO - Yecky Nuranditasari; Hera Widyastuti (Journal of Civil Engineering, 2023)
The hospital is one type of land use utilization which could cause vehicle attraction. It is estimated that the existence of the new Ar-Rozy Hospital would become a trip attraction. For this reason, it is necessary to conduct research to anticipate the magnitude of the movement attraction which would occur in the future due to the existence of the new Ar-Rozy Hospital. This study uses trip generation analysis at 3 existing hospitals located around downtown Probolinggo. The primary data used is a survey of vehicles entering and leaving the hospital, and the secondary one is data consisting of the number of polys, the number of practicing doctors, the number of medical staff, land area, number of rooms, number of beds. The result shows that all independent variables affect the occurrence of vehicle attraction. The best model suitable for representing the conditions of the hospital vehicle attraction is chosen based on the results of a significant regression model and consideration of the highest R2, multicollinearity, and normality test, the best model is : Y = 91.754 + 0.623 medical staff R2 = 0.991.